Pengaruh Budaya Terhadap Sifat Altruistik Konsumen Indonesia - Hasany, Tifani Dame; Safitri, Dhanny; Cahyaningrum, Dinis; Kuntary Ibrahim, Isra Dewi; Asri, Ni Wayan Adelia Mutiara (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study explores altruistic consumer behavior in Indonesia from a cultural perspective, emphasizing how collectivist values, religiosity, and social norms shape prosocial consumption. Using a narrative literature review, the research synthesizes theoretical and empirical findings from national and international journals to explain the interaction between traditional cultural values and modern consumer behavior. The results indicate that Indonesia’s collectivist culture (gotong royong or mutual cooperation, solidarity, and social responsibility) significantly fosters altruistic tendencies among consumers. Furthermore, religiosity acts as a moral and spiritual motivator that extends altruism into everyday consumption practices, including donations and ethical purchasing. The rise of digital platforms also enables the transformation of traditional solidarity into digital philanthropy and online social campaigns. Overall, altruistic consumer behavior in Indonesia emerges as a dynamic interplay between traditional culture, religious ethics, and modern technological adaptation.